Thermosensitive Cu2O–PNIPAM core–shell nanoreactors with tunable photocatalytic activity. Issue 24 (7th June 2016) - Jia, He; Roa, Rafael; Angioletti-Uberti, Stefano; Henzler, Katja; Ott, Andreas; Lin, Xianzhong; Möser, Jannik; Kochovski, Zdravko; Schnegg, Alexander; Dzubiella, Joachim; Ballauff, Matthias; Lu, Yan
Abstract : Cu2 O–PNIPAM core–shell nanoparticles have been synthesized to protect Cu2 O nanocubes from oxidation and applied as active "nanoreactors" with tunable catalytic activity with temperature for the photocatalytic decomposition of methyl orange. Abstract : We report a facile and novel method for the fabrication of Cu2 O@PNIPAM core–shell nanoreactors using Cu2 O nanocubes as the core. The PNIPAM shell not only effectively protects the Cu2 O nanocubes from oxidation, but also improves the colloidal stability of the system. The Cu2 O@PNIPAM core–shell microgels can work efficiently as a photocatalyst for the decomposition of methyl orange under visible light. A significant enhancement in the catalytic activity has been observed for the core–shell microgels compared with that of pure Cu2 O nanocubes. Most importantly, the photocatalytic activity of the Cu2 O nanocubes can be further tuned by the thermosensitive PNIPAM shell, as rationalized by our recent theory.